Proceedings of the Twenty-First Symposium on Electrical Insulating Materials
DOI: 10.1109/iseim.1988.763453
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of a uniaxially orientated polyethylene tape/oil insulating system under electrical and thermal stresses

Abstract: A u n i a x i a l l y o r i e n t a t e d polyethylene (UOPEJ t a p e has been used f o r t h e p r e s e n t series of experiments. A s e r i e s of experiments were conducted i n t o the e f f e c t of e l e c t r i c a l and thermal s t r e s s e s on t h e t a p e . IMTRODUCTION A u n i a x i a l l y o r i e n t a t e d polyethylene (UOPE) t a p e was developed by Brookhaven

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 1 publication
3
7
0
Order By: Relevance
“…Previous work on this has shown that the AC breakdown strength of a polypropylene laminated paper/oil combination decreases as swelling worsens [37]. Similar conclusions were reached with another composite insulating system consisting of UOPE/DDB oil [33][34][35]. In [38], the problem of solid/liquid combination was attacked from another angle, namely that of the interface and also in terms of the water content.…”
Section: Impregnation Effectsupporting
confidence: 70%
See 3 more Smart Citations
“…Previous work on this has shown that the AC breakdown strength of a polypropylene laminated paper/oil combination decreases as swelling worsens [37]. Similar conclusions were reached with another composite insulating system consisting of UOPE/DDB oil [33][34][35]. In [38], the problem of solid/liquid combination was attacked from another angle, namely that of the interface and also in terms of the water content.…”
Section: Impregnation Effectsupporting
confidence: 70%
“…A combination of polymer and of a low viscosity absorbing liquid was proposed several years ago. That was a combination of uniaxially orientated polyethylene (UOPE) and dodecylbenzene (DDB) oil [33][34][35]. Experimental results indicated that since collision impact of electrons accelerated in the free volume is the dominant cause for electrical tree initiation, liquid impregnation is a promising way to improve the performance of polymeric materials and to rise the breakdown strength [36].…”
Section: Impregnation Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…This, however, depends on the nature of the fluid. Other insulating liquids release gas bubbles, whereas others absorb gas bubbles, as was noted in [8,35]. Besides the factors, it would be fitting to add that for some of the liquids mentioned above, there are serious objections.…”
Section: Factors That May Influence the Behavior Of Insulating Liquidsmentioning
confidence: 96%